New description of metastable hcp phase for unaries Fe and Mn: Coupling between first‐principles calculations and CALPHAD modeling. Issue 9 (23rd May 2016) - Bigdeli, Sedigheh; Ehtehsami, Hossein; Chen, Qing; Mao, Huahai; Korzhavy, Pavel; Selleby, Malin
Abstract: The main focus in developing the third generation of CALPHAD databases is to model thermodynamic properties of materials by using models which are more physically based and valid down to 0 K. First‐principles calculations are helpful to choose and validate those models. Reliable calculation results, for example, at very low temperatures or on metastable systems reveal physical facts which might be inaccessible by experiments. Following our earlier work for modeling thermodynamic properties of pure elements (i.e., Fe and Mn) in third‐generation CALPHAD databases, the ε (hcp) phase was modeled as a metastable phase in the present work. Although hcp phase is just observed in these two elements under ultra‐high pressure, in the binary Fe–Mn this phase is metastable at ambient temperatures and pressures. Therefore, it should be properly modeled in unaries for later optimization of binary systems. Based on density functional theory (DFT) calculations, the magnetic ground state and the magnetic properties of ε ‐Fe, ε ‐Mn, and their binary solution phase were calculated. It was found that ε ‐Fe is anti‐ferromagnetic (type II) while ε ‐Mn has a paramagnetic ground state. Accordingly, magnetic contributions to thermodynamic properties were accurately modeled. Moreover, by means of the extrapolation of experimental data for the thermodynamic properties of binary systems and high‐pressure data for unaries, the metastable hcp phases at ambient pressure were modeled for the third‐generation CALPHAD database, consistently with other stable phases in the elements Fe and Mn.